2005
DOI: 10.1180/0026461056950277
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of patterns of copper and lead mineralization in human skeletons excavated from an ancient mining and smelting centre in the Jordanian desert: a reconnaissance study

Abstract: In this reconnaissance study, skeletal materials from people, dating from ∼1500 B.P., who lived by or worked at the ancient copper mines and furnaces of the Wadi Faynan in southern Jordan, were analysed using atomic absorption spectrophotometry (AAS) to determine the intensities of accumulation of copper and lead in their bones. Many of the bones analysed contained concentrations of these metals which are comparable to those of modern individuals who are heavily exposed to metals through contemporary industria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…The average bone/soil ratio of As calculated as 2.5:1. The _ Ikiztepe bone/soil ratio is considerably lower than the values of Grattan et al (2002Grattan et al ( , 2005. However, it is comparable with that of Oakberg et al (2000) (our calculation is 7.3:1 but it was calculated as 3:1 by Grattan et al, 2005 and as 9.5:1 by Grattan et al, 2002), in which arsenic was diagenetic in origin (Pike and Richards, 2002).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…The average bone/soil ratio of As calculated as 2.5:1. The _ Ikiztepe bone/soil ratio is considerably lower than the values of Grattan et al (2002Grattan et al ( , 2005. However, it is comparable with that of Oakberg et al (2000) (our calculation is 7.3:1 but it was calculated as 3:1 by Grattan et al, 2005 and as 9.5:1 by Grattan et al, 2002), in which arsenic was diagenetic in origin (Pike and Richards, 2002).…”
Section: Discussionmentioning
confidence: 57%
“…Gonzá lez-Remíers et al (2001, 2003 reported copper and lead data obtained from a geographically remote and uncontaminated ancient human population of the Canary Islands. Grattan et al (2002Grattan et al ( , 2005 and Pyatt et al (2005) highlighted the correlation between copper and lead concentrations in bones and the degree of environmental pollution as a result of the development of the mining industry and metalliferous processing in one of the metallurgical centers of the ancient world, the Wadi Faynan. Drasch (1982) and Nriagu et al (cited in Grattan et al, 2002) emphasize the lead uptake originating from the utensils used in the Roman populations.…”
Section: Introductionmentioning
confidence: 98%
“…The charcoal residues around the Roman mines demonstrate that fuelwood had to be brought down from the plateau because the Faynan landscape had been stripped bare of timber (Engel, 1993;Engel and Frey, 1996). The geochemical studies indicate extraordinarily high levels of heavy metal pollutants in the Khirbat Faynan barrage sediments in the Roman and Byzantine centuries, many times higher than modern safe limits , and in the skeletons of people buried around Khirbat Faynan at this time (Grattan et al, 2005). The intense smelting activity around Khirbat Faynan produced a dense pall of airborne pollution that affected plants, animals and people.…”
Section: Roman Imperialism and Its Aftermathmentioning
confidence: 96%
“…Previous studies have shown that comparisons of measurements of soil surrounding bone, as well as the interior and exterior of long bones (cf. Grattan et al, 2005) are an insufficient control for measuring diagenetic uptake (Pike and Richards, 2002). In this study, we present a method to control for post-depositional diagenetic uptake of trace elements versus the bioaccumulation of these elements during the lifespans of the individuals interred at the cemetery.…”
Section: Introductionmentioning
confidence: 99%